2014
DOI: 10.3109/10428194.2014.951847
|View full text |Cite
|
Sign up to set email alerts
|

Primary intravascular natural killer/T cell lymphoma of the central nervous system

Abstract: Intravascular lymphoma (IVL) is a rare neoplasm charac terized by proliferation of malignant cells within the small vessel lumina, particularly capillaries. Cases of IVL almost always occur in extranodal sites, including the skin, cen tral nervous system (CNS), bone marrow, lung and liver [1,2]. B-cell lineage lymphoma is the major variant in IVL, accounting for approximately 85-90% of cases of IVL [3]. Intravascular natural killer (NK)/T cell lymphoma (IVNKTL) is regarded as a rare variant, involving mostly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Recently, Deetz et al and Metcalf et al reported that the vessels associated with intravascular anaplastic large cell lymphoma were actually D2‐40 positive, whereas those associated with intravascular NK/T‐cell lymphoma cases were D2‐40 negative . More importantly, all of the reported intravascular anaplastic large cell lymphoma cases were EBV‐negative, whereas nearly all of the reported intravascular NK/T‐cell lymphoma cases were EBV‐positive . According to these results, intravascular anaplastic large cell lymphoma actually appears to be intralymphatic anaplastic large cell lymphoma, and its growth pattern is very similar to the intravascular pattern observed with cutaneous metastasis …”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Recently, Deetz et al and Metcalf et al reported that the vessels associated with intravascular anaplastic large cell lymphoma were actually D2‐40 positive, whereas those associated with intravascular NK/T‐cell lymphoma cases were D2‐40 negative . More importantly, all of the reported intravascular anaplastic large cell lymphoma cases were EBV‐negative, whereas nearly all of the reported intravascular NK/T‐cell lymphoma cases were EBV‐positive . According to these results, intravascular anaplastic large cell lymphoma actually appears to be intralymphatic anaplastic large cell lymphoma, and its growth pattern is very similar to the intravascular pattern observed with cutaneous metastasis …”
Section: Discussionmentioning
confidence: 54%
“…Given that one of our cases presented with positive CD30 staining, intravascular NK/T‐cell lymphoma should be distinguished from intravascular anaplastic large cell lymphoma; the latter is characterized by anaplastic cells with prominent polymorphisms, whereas the former features medium‐sized and rather uniform hyperchromatic cells . The neoplastic cells found in intravascular anaplastic large cell lymphomas usually occlude the vessels and form closely packed nodules, whereas the neoplastic cells found in intravascular NK/T‐cell lymphomas are usually scattered within the vessels .…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations